Using the eSexual Health Clinic to access chlamydia treatment and care via the internet: a qualitative interview study. (7th October 2017) - Aicken, Catherine R H; Sutcliffe, Lorna J; Gibbs, Jo; Tickle, Laura J; Hone, Kate; Harding-Esch, Emma M; Mercer, Catherine H; Sonnenberg, Pam; Sadiq, S Tariq; Estcourt, Claudia S; Shahmanesh, Maryam
Abstract : Objective: We developed the eSexual Health Clinic (eSHC), an innovative, complex clinical and public health intervention, embedded within a specialist sexual health service. Patients with genital chlamydia access their results online and are offered medical management via an automated online clinical consultation, leading to antibiotic collection from community pharmacy. A telephone helpline, staffed by Sexual Health Advisers, is available to support patients and direct them to conventional services if appropriate. We sought to understand how patients used this ehealth intervention. Methods: Within exploratory studies of the eSHC (2014–2015), we conducted in-depth interviews with a purposive sample of 36 patients diagnosed with chlamydia, who had chosen to use the eSHC (age 18–35, 20 female, 16 male). Thematic analysis was conducted. Results: Participants described choosing to use this ehealth intervention to obtain treatment rapidly, conveniently and privately, within busy lifestyles that hindered clinic access. They described completing the online consultation promptly, discreetly and with ease. The information provided online was considered comprehensive, reassuring and helpful, but some overlooked it in their haste to obtain treatment. Participants generally described being able to collect treatment from pharmacies discreetly and promptly, but for some, poor awareness of the eSHC by pharmacy staff undermined their ability to do this. Those unsuitable for remote management, who were directed to clinic, described frustration and concern about health implications and clinic attendance. However, the helpline was a highly valued source of information, assistance and support. Conclusion: The eSHC is a promising adjunct to traditional care. Its users have high expectations for convenience, speed and privacy, which may be compromised when transitioning from online to face-to-face elements of the eSHC. Managing expectations and improving implementation of the pharmacy process, could improve their experiences. Positive views on the helpline provide further support for embedding this ehealth intervention within a specialist clinical service.